Respuesta :

Answer:

A. x^2 + 6

Step-by-step explanation:

(4x^2 - 6x + 8) - (3x^2 - 6x + 2) =

The first set of parentheses is unnecessary, so just remove it.

= 4x^2 - 6x + 8 - (3x^2 - 6x + 2)

To remove the second set of parentheses, change the sign of each term inside.

= 4x^2 - 6x + 8 - 3x^2 + 6x - 2

Now combine like terms.

= x^2 + 6

For this case we must find the difference of the following polynomials:

[tex](4x ^ 2-6x + 8) - (3x ^ 2-6x + 2) =[/tex]

Taking into account that:

[tex]- * - = +\\+ * - = -[/tex]

We have:

[tex]4x ^ 2-6x + 8-3x ^ 2 + 6x-2 =\\x ^ 2 + 0x + 6 =\\x ^ 2 + 6[/tex]

Answer:

[tex]x ^ 2 + 6[/tex]